(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article systematically analyzes the philosophical and legal foundations of inclusive education. It highlights the reliance of the idea of inclusion on the principles of humanity, equality and social justice. It reveals the stages of development of inclusive education based on international and national regulatory and legal documents. It also outlines the legal mechanisms and prospects for the implementation of inclusive education in the Republic of Uzbekistan.